2017
DOI: 10.1371/journal.pone.0173243
|View full text |Cite
|
Sign up to set email alerts
|

High HIV prevalence and incidence among women in Southern Mozambique: Evidence from the MDP microbicide feasibility study

Abstract: BackgroundThe study aimed to assess the feasibility of conducting large scale HIV prevention clinical trials in Mozambique by measuring HIV prevalence and incidence among women of reproductive age. This paper describes the baseline socio-demographic characteristics of the Mozambique Microbicides Development Programme (MDP) feasibility cohort, baseline prevalence of HIV and other STIs, and HIV incidence.MethodsThe Mozambique MDP feasibility study was conducted from September 2007 to August 2009 in urban Mavalan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
4
8
0
1
Order By: Relevance
“…The regional disparity in HIV infection was observed in this study. Similar findings have been reported in previous studies [ 44 , 45 ]. Women in the northern provinces of Cabo Delgado and Nampula had lower odds of HIV infection, while women in the southern provinces were more likely to have HIV infection [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…The regional disparity in HIV infection was observed in this study. Similar findings have been reported in previous studies [ 44 , 45 ]. Women in the northern provinces of Cabo Delgado and Nampula had lower odds of HIV infection, while women in the southern provinces were more likely to have HIV infection [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study the prevalence of TV was noticed 11% in cases. This finding is in concordance with several previous studies 29,30 from different regions of the world, while in contrast to another study in Syrian population 31,32 .…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have also reported risk factors for HIV to include multiple sexual partners [10][11][12], extramarital sex [10], intimate partner violence [13][14][15], poverty or household wealth [16], and infrequent or lack of condom use [10,17]. Others include religion, [18] having an untreated sexually transmitted infection such as herpes simplex virus type 2, mobility and migration, [19] and ruralurban residence status [16,19]. Despite the significant strides made by Mozambique, HIV prevalence remains high with an increasing number of new infections.…”
Section: Introductionmentioning
confidence: 99%